DEVELOPMENT OF MILLET-BASED RECIPES UTILISING POTATO STARCH, RICE FLOUR AND ARROWROOT POWDER AS THICKENING AGENTS - T. GAYATRI (The Journal of Research ANGRAU, 2025)
The present study aimed to develop value-added products from selected millets by  incorporating plant-based, gluten-free starches. Conducted in 2023 at St. Joseph’s College for Women, Visakhapatnam, the research focused on four millet varieties: Barnyard, Kodo, Little and Foxtail. Three plant-derived starches—potato starch, arrowroot powder and rice flour were used to enhance the functional and sensory properties of millet-based recipes. The developed products included Barnyard Cutlet, Kodo Steam Cake, Little Millet Soup and Foxtail Papad. Each product was prepared in three variations, using the different starches.Sensory evaluation was conducted using a 9-point hedonic scale. Among the Barnyard Cutlet variations, the rice flour version scored highest for aroma, while the arrowroot-based cutlet was rated best in appearance. Little Millet Soup received consistent ratings across all three starch variations for aroma, aftertaste, and overall acceptability. The Kodo Steam Cake prepared with potato starch received the lowest scores in most parameters, except for appearance, which was rated favourably.In addition to sensory analysis, a line spread test was conducted to assess the viscosity of the starches. The results showed that rice flour had the highest spread ability, indicating lower viscosity, while arrowroot powder showed the least spread, suggesting it is a stronger thickening agent. Moisture content was also analysed, as it plays a critical role in determining the structural and functional properties of food products. Based on loss-on-drying results, arrowroot powder exhibited the highest moisture content among the starches tested.